Formulation and Evaluation of Herbal Soaps: A Comprehensive Review of Natural Ingredients and Approaches - Shivani Raj; Alpana Kumari; Indrajeet Kumar (International Journal of Scientific Research in Science and Technology, 2025)
The largest sensory organ in the body, the skin has defensive properties and is essential for preserving homeostasis. But a number of things, including exposure to the environment, infections caused by bacteria, and chemical irritants, can result in skin conditions that negatively impact one's health and quality of life. Despite their widespread usage in personal care and cleaning, conventional synthetic soaps can include harsh chemicals that might cause irritation, lack of moisture, or long-term negative effects. However, because of their antibacterial, antioxidant, anti-inflammatory, and wound-healing qualities, herbal soaps made from natural plant extracts and essential oils provide a safer and more advantageous option. The phytoconstituents found in herbal soaps, such as terpenes, alkaloids, flavonoids, and phenolic compounds, help to nourish, protect, and rejuvenate skin. In soap compositions, common herbs like as curry leaves, neem, turmeric, Tulsi, aloe vera, and rose are widely used for their medicinal properties. In order to ensure skin compatibility and washing effectiveness, herbal extracts and essential oils are added to natural soap bases throughout the production process. Organoleptic evaluations (colour, Odor, appearance, texture, and hardness) and physicochemical evaluations (pH, foam height, retention, total fatty matter (TFM), moisture content, and alcohol-insoluble matter) are used to evaluate herbal soaps. The natural origin, cost-effectiveness, safety, and environmental sustainability of herbal soaps make them a viable substitute for synthetic products, with potential uses in the cosmetic and medical industries.
Keywords: Phytoconstituent; Antioxidant; Antibacterial